Obesity decreases B cell responses in young and elderly individuals. Issue 3 (9th February 2016) - Frasca, Daniela; Ferracci, Franco; Diaz, Alain; Romero, Maria; Lechner, Suzanne; Blomberg, Bonnie B.
Abstract : Objective: To evaluate the effects of obesity‐associated inflammation on influenza vaccine responses. Methods: In young and elderly individuals, both lean and with obesity, antibody responses to influenza vaccination were measured. Results: A decrease in in vivo vaccine responses, circulating switched memory, and transitional B cells and an increase in pro‐inflammatory late/exhausted memory B cells were found. In vitro B cell function was measured by activation‐induced cytidine deaminase and E47, markers of optimal antibody responses. Moreover, IL‐6 production was increased, whereas IL‐10 production was decreased in cultures of B cells from individuals with obesity. Markers of immune activation (TNF‐α, TLR4, micro‐RNAs) in unstimulated B cells were also found increased and were negatively correlated with B cell function. In order to reveal potential mechanisms, we stimulated B cells from lean individuals in vitro with leptin, the adipokine increased in obesity. Leptin increased phospho‐STAT3, crucial for TNF‐α production, and decreased phospho‐AMPK, the energy sensing enzyme upstream of phospho‐p38 MAPK and E47. Leptin‐induced phospho‐STAT3 and phospho‐AMPK levels were similar to those in B cells from individuals with obesity. Conclusions: These results demonstrate that leptin can be responsible for decreased B cell function in obesity.